2005
DOI: 10.1242/dev.02167
|View full text |Cite
|
Sign up to set email alerts
|

Ptf1a determines GABAergic over glutamatergic neuronal cell fate in the spinal cord dorsal horn

Abstract: Mutations in the human and mouse PTF1A/Ptf1a genes result in permanent diabetes mellitus and cerebellar agenesis. We show that Ptf1a is present in precursors to GABAergic neurons in spinal cord dorsal horn as well as the cerebellum. A null mutation in Ptf1a reveals its requirement for the dorsal horn GABAergic neurons. Specifically, Ptf1a is required for the generation of early-born (dI4, E10.5) and late-born (dILA, E12.5)dorsal interneuron populations identified by homeodomain factors Lhx1/5 and Pax2. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
283
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(298 citation statements)
references
References 37 publications
12
283
1
2
Order By: Relevance
“…Our study of Lhx1 and Lhx5, together with recent studies of Ptf1a (18,19,49), suggests that similar mechanisms of transcriptional regulation may operate in the cerebellum and the spinal cord to control the generation of specific types of neurons. In the cerebellum, Ptf1a is required for the specification of progenitors of all GABAergic neurons, including Purkinje cells (18,19), in which Lhx1 and Lhx5 are expressed and required for their normal differentiation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our study of Lhx1 and Lhx5, together with recent studies of Ptf1a (18,19,49), suggests that similar mechanisms of transcriptional regulation may operate in the cerebellum and the spinal cord to control the generation of specific types of neurons. In the cerebellum, Ptf1a is required for the specification of progenitors of all GABAergic neurons, including Purkinje cells (18,19), in which Lhx1 and Lhx5 are expressed and required for their normal differentiation.…”
Section: Discussionsupporting
confidence: 58%
“…In the cerebellum, Ptf1a is required for the specification of progenitors of all GABAergic neurons, including Purkinje cells (18,19), in which Lhx1 and Lhx5 are expressed and required for their normal differentiation. Ptf1a and Lhx1/ Lhx5 also are involved in the generation of subsets of GABAergic interneurons in the dorsal spinal cord (48,49). Ptf1a and Lhx1/Lhx5 thus seem to function at sequential steps in a same genetic program that controls the generation of specific neuronal cell types in different regions of the developing central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Ptf1a is expressed in several regions of the developing nervous system (14,29). We show here that in the cerebellum, Ptf1a mRNA and protein are expressed in the VZ at E12-E14 and, at perinatal stages, in white matter cells (presumably interneuronal progenitors).…”
Section: Ptf1a Is Expressed In Progenitors Of Pcs and Interneuronsmentioning
confidence: 61%
“…A recent study has shown that a 300-kb deletion in the enhancer of the Ptf1a gene leads to abnormal cerebellar development as well as loss of PCs and interneurons (7). Ptf1a is also required for the generation of dorsal horn GABAergic interneurons in the spinal cord, and, in its absence, Ptf1a-derived cells adopt a glutamatergic phenotype (14). A recent study in the retina shows that inactivation of Ptf1a leads to a fate switch in horizontal and amacrine cell precursors that causes them to adopt a ganglion cell fate (15).…”
mentioning
confidence: 99%
“…Similar to other sites, in the cerebellum, projection neurons are generated first, and local interneurons follow. In addition, transcription factors relevant for the specification of cerebellar GABAergic types, such as Ptf1-a or Pax-2, also participate to the same processes in other CNS regions [7,8,32,[57][58][59][60]. Nevertheless, a common theme in the genesis of interneurons along the neuraxis is that different phenotypes are generated from distinct subsets of fate-committed progenitors.…”
Section: Concluding Remarks: a Peculiar Neurogenic Strategymentioning
confidence: 99%